2021
DOI: 10.1177/14604582211020064
|View full text |Cite
|
Sign up to set email alerts
|

Rural use of health service and telemedicine during COVID-19: The role of access and eHealth literacy

Abstract: The COVID-19 pandemic has driven a greater reliance on telemedicine, yet rural access, use, and satisfaction with telemedicine and the role of eHealth literacy are unknown. Using a cross-sectional design, 279 (70.6% female) western rural Canadians completed an online survey. The majority of participants reported access to telemedicine, but nearly 1/5 lacked access to online or virtual mental health services. The majority of participants had used health care services following the declared COVID-19 pandemic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 29 publications
1
38
1
3
Order By: Relevance
“…The negative correlation found between age and satisfaction with telemedicine is consistent with previous studies that showed the difficulties faced by the elderly with access to the internet and telemedicine [38,39], including studies conducting during the COVID-19 period [40][41][42]. The positive correlation between eHealth literacy and satisfaction with telemedicine was also supported by previous research studies [43,44].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The negative correlation found between age and satisfaction with telemedicine is consistent with previous studies that showed the difficulties faced by the elderly with access to the internet and telemedicine [38,39], including studies conducting during the COVID-19 period [40][41][42]. The positive correlation between eHealth literacy and satisfaction with telemedicine was also supported by previous research studies [43,44].…”
Section: Discussionsupporting
confidence: 89%
“…Women tend to search for more healthcare information than men and use telemedicine more, as per Horrell et al [36] who found that 50% of the women used telemedicine compared with 43% of the men, and expressed greater satisfaction with telemedicine [43]. On many occasions, it is the women in the family who are responsible for overall family health, so they are the ones who contact the physicians on behalf of other family members [45].…”
Section: Discussionmentioning
confidence: 99%
“…Patients from rural areas of BC have indicated high satisfaction with telehealth. They have a preference for video over phone visits and for telehealth as a supplement to rather than a replacement for in-person visits [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, smart healthcare services play an important role in diagnosing infectious diseases and reducing the risk of cross-contamination caused by face-to-face contact. For example, during COVID-19, patients have showed a higher willingness to use video consultations than before (37). Based on telemedicine service systems and intelligent medical robots, patients can be classified, evaluated, monitored, and treated within a safe distance, which reduces the risk of frontline medical staff infected with COVID-19.…”
Section: Theoretical Underpinning and Hypotheses Developmentmentioning
confidence: 99%